Immunisation of cattle against somatostatin: effects on carcass composition and the responsiveness of viable fat explants to digestive tract hormones - Baba, A.S.H.; Sembiring, M.; Shafit, H.; Zainur, A.S. (2000)
Kedah-Kelantan cattle were immunised against somatostatin (SS) and the animals slaughtered on the 45th week. Viable fat expiants were cultured in vitro in the presence of insulin (10 -10 M), cholecystokinin (CCK), gastric inhibitory polypeptide (GIF), glucagon-like polypeptide (7-35) (GLP-1) or SS (each at 10 -9 M) and the rate of lipogenesis determined. Immunisation had no effect (P>0.05) on growth performance, feed conversion .ratio or carcass weight (P>0.05). SS-immunised cattle had lower (P<0.05) carcass fat for perirenal, pelvic, breast and subcutaneous back fat than control animals. Perirenal, subcutaneous tail and subcutaneous back fats taken from control animals responded positively (61.2%, 72.1% and 60.0% respectively; P<0.05)) to insulin action. Fat expiants from SS-immunised animals however, had reduced responsiveness to insulin stimulation (P>0.05). CCK and GLP-1 stimulated (P<0.05) lipogenesis of fat expiants taken from subcutaneous back and tail fat but this effect was not observed when fat expiants from SS-immunised animals were used. SS inhibited perirenal fat lipogenesis (P<0.05) but stimulated (P>0.05) both subcutaneous back fat and subcutaneous tail fat lipogenesis. These effects were diminished for SS-immunised animals. GLP-1 did not affect subcutaneous back fat and perirenal fat in either treatment group. The effects of immunisation against SS on carcass composition may be mediated by changes in fat tissue responsiveness to hormones from the digestive tract.